2020
DOI: 10.3390/membranes10080179
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study on Direct Contact Membrane Distillation Modules for High-Concentration NaCl Solution

Abstract: Membrane distillation technology, as a new membrane-based water treatment technology that combines the membrane technology and evaporation process, has the advantages of using low-grade heat, working at atmospheric pressure with simple configuration, etc. In this study, heat and mass transfer were coupled at the membrane surfaces through the user-defined function program. The effects of feed temperature, feed velocity and permeate velocity on temperature polarization were mainly investigated for a high-concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…(1) The temperature polarization increases with the increase of the feed temperature and the decrease of the feed velocity and penetration velocity; The counter-current operation is better than the co-current operation in most cases, except for relatively low NaCl concentrations or sufficiently long module lengths [15].…”
Section: Research Contents Conclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…(1) The temperature polarization increases with the increase of the feed temperature and the decrease of the feed velocity and penetration velocity; The counter-current operation is better than the co-current operation in most cases, except for relatively low NaCl concentrations or sufficiently long module lengths [15].…”
Section: Research Contents Conclusionmentioning
confidence: 99%
“…(2) The optimal membrane thickness is between 10-20 μm, which corresponds to the selected materials, pore size distribution and the maximum permeability flux under the operating conditions. The membrane materials with low thermal conductivity and high porosity are easily obtain higher permeation flux and larger optimal membrane thickness, while the optimal membrane thickness can be reduced by increasing the feeding speed or temperature [15].…”
Section: Research Contents Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ahmad et al [13] studied the RIS model for osmotic membrane evaporation of fruit juices and found that physical properties like viscosity and density variations during the process had a significant effect on water flux. Ni et al [22] studied the effect of temperature polarization in direct contact membrane distillation for NaCl concentration and observed that temperature polarization was enhanced with the increase of feed temperature and the decrease of feed and permeate velocity. Similarly, Lou et al [23] investigated coupled temperature and concentration polarization in the membrane distillation treatment of brines with the help of the CFD heat and mass transfer model and observed the effect of coupled temperature and concentration polarization.…”
Section: Introductionmentioning
confidence: 99%